Transport of Russian Federation: Problems and Trend of Its Development - Ilya Gennadievich Tkachev (Управленческое консультирование, 2018)
The article presents the analysis of the development of transport of Russian Federation on the present stage using a set of indicators in dynamics: the number of transport organizations, revenues and profits, the volume of cargo and passengers, length of the transport ways, number of transport vehicles, investment in fixed capital; the analysis of the main documents for development of the transport complex; the main trends and problems of development of transport of the country.